Loaves, Beds, Plants and Osiris - Roeten, Leo (Archaeopress Egyptology Ser., 2019)
The emergence of the cult of Osiris is generally posited to have occurred quite suddenly at the end of the 5th dynasty. This study considers evidence to suggest this appearance was preceded by a period of development of the theology and mythology of the cult.